- #1

AAQIB IQBAL

- 11

- 0

When we calculate the first derivative we put a = r.cos(theta), b = r.sin(theta) (every thing is ok till here)

My confusion starts when we use (theta) = tan^-1(b/a) [tan inverse]

the reason for my confusion can be understood by:

suppose we have a = -1, b = 1

we put a = sqrt{2}*cos(3*pi/4)

b = sqrt{2}*sin(3*pi/4)

but the tan^-1(b/a) = tan^-1(-1) = -pi/4

but our theta is 3*pi/4

according to this theta our a will be 1 and b will be -1 which is different from our values of a and b